(untitled) (Modern Problems of Metallurgy, 2019)
Density is an important physical characteristic of ferroalloys, since it determines the possibility of its immersion in liquid steel and provides favorable conditions for melting. Industrial ferroalloys are divided by their density into light (ferrous silicocalcium, high silicon ferrosilicon), heavy (ferrofiber, ferromolybdenum) and close to the metal melt (silicomanganese, silicochromium). The urgency of solving the problem of increasing the processability of FS65 ferrosilicon (the density of its lump fractions is comparable to the density of slag) is related to the ratio of its density and the density of the slag-metal melt. In order to improve the manufacturability of small fractional ferrosilicon, which is accumulated annually in the process of producing ferroalloys, we tested its briquetting with the addition of “weighting agents” (metal chips) and carried out their experimental application. The results of the laboratory test of briquetting of fractional ferrosilicon FS65 with the addition of a weighing agent for improving the technological efficiency of use in the production of steel and evaluated characteristics, as well as the duration and conditions of melting briquettes are presented